Substance P Increases the Excitability of Dorsal Motor Nucleus of the Vagus Nerve via Inhibition of Potassium Channels - Yang, Eunhee; Kim, Woojin; Park, Yong Seek; Jin, Young-Ho (Frontiers in Neuroscience, 2022)
Substance P (SP) concentration increases in the medial portion dorsal motor nucleus of vagus (mDMV) in the brain stem are closely associated with chemotherapy induce nausea and vomiting (CINV). However, the underlying cellular and molecular mechanisms of action have not been well understood. In this study, we investigated SP effect on mDMV neurons using whole-cell patch-clamp recordings from rat brainstem slices. Application of SP induced tonic and phasic responses in different concentration ranges. Sub-micromolar concentrations of SP induced an inward shift of the holding current by increasing membrane input resistance. The response was mimicked by acidification of the extracellular solution and inhibited by a neurokinin type 1 receptor antagonist. Those responses have equilibrium potentials close to the K+ equilibrium potential. In addition, a TWIK-related acid-sensitive K+ channel 3 (TASK-3) inhibitor, PK-THPP, induced responses similar to that produced by sub-micromolar SP. Meanwhile, micromolar concentrations of SP facilitated GABA release but diminished glutamate release and that was blocked by a neurokinin type 3 receptor antagonist and GABAB receptor antagonist, respectively. In a current-clamp recordings, sub-micromolar SP increased neuronal excitability by depolarizing membrane potentials. However, neither of the elevation of the SP concentration to micromolar ranges nor cumulative addition of GABAA and ionotropic glutamate receptor antagonists affected neuronal excitability. Thus, SP increases excitability of the mDMV neurons by inhibition of TASK-3 leak K+ current.